Exoscope and operative microscope for training in microneurosurgery: A laboratory investigation on a model of cranial approach - Calloni, Tommaso; Antolini, Laura; Roumy, Louis-Georges; Nicolosi, Federico; Carrabba, Giorgio G.; Di Cristofori, Andrea; Fontanella, Marco M.; Giussani, Carlo G. (Frontiers in Surgery, 2023)
Objective To evaluate the viability of exoscopes in the context of neurosurgical education and compare the use of a 4k3D exoscope to a traditional operative microscope in the execution of a task of anatomic structure identification on a model of cranial approach. Material and methods A cohort of volunteer residents performed a task of anatomical structure identification with both devices three times across an experimental period of 2 months. We timed the residents’ performances, and the times achieved were analyzed. The volunteers answered two questionnaires concerning their opinions of the two devices. Results Across tries, execution speed improved for the whole cohort. When using the exoscopes, residents were quicker to identify a single anatomical structure starting from outside the surgical field when deep structures were included in the pool. In all other settings, the two devices did not differ in a statistically significant manner. The volunteers described the exoscope as superior to the microscope in all the aspects the questionnaires inquired about, besides the depth of field perception, which was felt to be better with the microscope. Volunteers furthermore showed overwhelming support for training on different devices and with models of surgical approaches. Conclusion The exoscope appeared to be non-inferior to the microscope in the execution of a task of timed identification of anatomical structures on a model of cranial approach carried out by our cohort of residents. In the questionnaires, the residents reported the exoscope to be superior to the microscope in eight of nine investigated domains. Further studies are needed to investigate the use of the exoscope in learning of microsurgical skills.